Quantifying Vulnerability to Poverty : A Proposed Measure, Applied to Indonesia - Pritchett, Lant; Suryahadi, Asep; Sumarto, Sudarno (World Bank, Washington, DC, 2015)
Vulnerability is an important aspect of households' experience of poverty. Many households, while not currently in poverty, recognize that they are vulnerable to events - a bad harvest, a lost job, an illness, and unexpected expense, an economic downturn - that could easily push them into poverty. Most operational measures define poverty as some function of the shortfall of current income, or consumption expenditures from a poverty line, and hence measure poverty only at a single point in time. The authors propose a simple expansion of those measures to quantify vulnerability to poverty. They define vulnerability as a probability, the risk that a household will experience at least one episode of poverty in the near future. A household is defined as vulnerable if it has 50-50 odds, or worse of falling into poverty. Using those definitions, they calculate the "vulnerability of poverty line" (VPL) as the level of expenditures below which a household is vulnerable to poverty. The VPL allows the calculation of a "headcount vulnerability rate" (the proportion of households vulnerable to poverty), a direct analogue of the "headcount poverty rate". The authors implement this approach using two sets of panel data from Indonesia. First they show that if the poverty line is set so that the headcount poverty rate is twenty percent, the proportion of households vulnerable to poverty is roughly 30-50 percent. In addition to the twenty percent currently poor, an additional 10-30 percent of the population is at substantial risk of poverty. They illustrate the usefulness of this approach for targeting, by examining differences in vulnerability between households by gender, level of education, urban-rural residence, land-holding status, and sector of occupation of the head of household.